1 ppm/°C bandgap with multipoint curvature‐compensation technique for HVIC. Issue 25 (1st December 2014) - Zhang, Yunwu; Zhu, Jing; Sun, Weifeng; Yang, Bang; Huang, Zexiang
Abstract : A high‐order curvature‐compensated current mode bandgap reference (BGR) over a very wide temperature range is presented. High‐order curvature correction for this reference is accomplished by the proposed multipoint corrected technique, which realises exponential curvature‐compensation terms in lower and higher temperature ranges separately through simple structures. The compact multipoint curvature‐compensation circuit cancels out the nonlinear terms of the BGR using sub‐threshold operated metal–oxide semiconductor field effect transistors, which subtract those currents that are proportional to the nonlinearity out of the reference voltage. As a result, a flattened and better effect of curvature compensation in a wide temperature range is realised. The circuit performance was verified experimentally. The measurements indicate that the proposed BGR can achieve a temperature coefficient as low as 1.01 ppm/°C over the temperature range of 160°C (−40 to 120°C).